Latitude- and depth-driven divergence in protist trophic strategies revealed by a machine learning model - Thomas, Elaina; Groussman, Mora J.; Coesel, Sacha N.; Hawco, Nicholas J.; Bundy, Randelle M.; Armbrust, E. Virginia (Frontiers in Microbiology, 2025)
Protists are ubiquitous across the ocean, holding different roles in the food web depending on their trophic capabilities. Many protists are mixotrophs, which are capable of both photosynthesizing and ingesting prey. However, there is limited knowledge of which protist species are mixotrophs in nature, as well as their activity and distribution throughout the ocean. Here, we present Marine PRotist In Situ trophic Mode predictor (MarPRISM), a refined XGBoost-based machine learning model for predicting the in situ trophic mode (phototrophy, mixotrophy, and heterotrophy) of marine protist species based on transcriptional profiles. We used MarPRISM to generate 1,462 trophic mode predictions for 28 environmental protist species based on 335 metatranscriptomes collected across the North Pacific Ocean, from the surface to 130 m depth, over the diel cycle, and within nutrient-amended incubations. Eight environmental species were identified as having mixotrophic capabilities, including six dinoflagellates, one bolidophyte, and one haptophyte. The species with mixotrophic capabilities varied in how they shifted their trophic mode across the surface ocean and in response to the experimental amendment of nitrate and iron. Limited light availability appeared to lead one species to shift from mixotrophy at the surface toward heterotrophy between 41 and 130 m depth. We used transcript abundance to evaluate the abundance of species with different trophic capabilities (species with mixotrophic capabilities, phototrophic specialists, and heterotrophic specialists). At the surface within the subtropical gyre, transcript abundance was similar among protist species with different trophic capabilities. In the gyre, the protist community was nitrate-limited, and experimental nitrate amendment favored phototrophic specialists. Increasing nitrate availability with latitude was correlated with phototrophic specialists being the dominant protist trophic group in the transition zone between the subtropical and subpolar gyres under high nitrogen availability. In contrast, under lower nitrogen conditions in the transition zone, protist species with different trophic capabilities comprised equal portions of the surface community. Light and nitrate availability influenced the transcript abundance of phototrophic specialists across depth; phototrophic specialists had high transcript abundance at 130 m in the subtropical gyre and at the surface in the transition zone, while species with mixotrophic capabilities and heterotrophic specialists showed less variation in transcript abundance with depth.